Effectiveness of project-based learning model on improving critical thinking skills and student creativity - Sungkono Sungkono; Firdiawan Ekaputra (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
The purpose of this study was to test (1) the effectiveness of the application of the project-based learning model on improving critical thinking skills (2) the effectiveness of the application of the project-based learning model on improving student creativity skills. The subjects used in this study were students who took the class B media script writing course at the Yogyakarta State University Educational Technology Study Program in the 2023/2024 academic year. This research is a quasi-experimental type of research with a one group pretest-posttest scheme design. Data on students' critical thinking skills and creativity were obtained using a questionnaire before and after the application of the project-based learning model in lecture activities. Data on critical thinking skills and student creativity were then tested using paired samples t test. The results of the paired samples t test found critical thinking ability and creativity each showed a value of 0.00. In this study, it can be concluded that (1) the application of the project-based learning model is effective in improving students' critical thinking skills (2) the application of the project-based learning model is effective in improving students' creativity.